A case of ectopic cervical thymoma with myasthenia gravis mimicking a parathyroid tumour. Issue 11 (25th October 2022) - Kamimura, Go; Ueda, Kazuhiro; Takeda, Aya; Miyata, Ryo; Aoki, Masaya; Nagata, Toshiyuki; Sato, Masami
Abstract: Reports of cervical thymoma with myasthenia gravis are rare. In addition, 99mTc‐MIBI (methoxyisobutylisonitrile:sestamibi) scintigraphy is a useful diagnostic examination for enlarged parathyroid tumours; however, there are a few reports of its accumulation in thymoma. Among them, there are no reports of cervical thymomas with 99mTc‐MIBI accumulation complicated by myasthenia gravis. In this study, we performed surgery on a patient with preoperative myasthenic crisis accompanied by a cervical thymoma and a parathyroid tumour. Preoperatively, the cervical mass was determined to be a parathyroid tumour and was complicated by myasthenia gravis without thymic tumour. However, a pathological examination revealed that the cervical tumour with 99mTc‐MIBI accumulation was a Type B2 thymoma, and a parathyroid tumour was identified in the vicinity. We report a very rare case in which symptoms improved with surgery. Abstract : We report an extremely rare case of cervical thymoma with 99mTcMIBI scintigraphic accumulation associated with myasthenia gravis that was difficult to diagnose and treat.